Ornamental Rocks from Tierra del Fuego - Picado, Estefanía; Barrionuevo, Federico Raúl
“Natural stone,” a term that is frequently applied to ornamental rocks, it encompasses a wide range of stone materials used in the building industry. These rocks have been used by man for the manufacturing of different tools since ancient times. Today, these materials are used as raw materials for the construction of civil works, cladding of buildings, squares and streets. Tierra del Fuego Province, southern Patagonia Argentina, has metamorphic igneous rock complex, product of the magmatism that affected the region during the Cretaceous. It is mainly composed of magmatic bodies of small dimensions, between 3 and 25 km2, and they are hosted by metasedimentary rocks of the Yahgán, Beauvoir and Lemaire Formations. The use of these natural resources has been evaluated only partially, with geotechnical tests, which resulted in very good data. In this work, the first laboratory tests performed on these rocks are detailed. Technological studies were focused on evaluating the suitability of several igneous materials for ornamental use. In specialized laboratories, different standardized petrophysical tests were performed to describe the properties of the rocks such as density, absorption and open porosity, resistance to compression and resistance to bending. Furthermore, the technological characteristics of the Fuegian rocks were contrasted with those published for other ornamental varieties marketed in Argentina. The level of geotechnical characterization reached allowed to establish that the Fuegian territory has different rocks susceptible to being used as ornamental rocks, among them the granitoids of the Cerro Jeu-Jepén stand out. Fil: Picado, Estefanía. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina Fil: Barrionuevo, Federico Raúl. Universidad Nacional de La Plata. Facultad de Ciencias ...